Engaging political histories of urban uprisings with young people: The Liverpool riots, 1981 and 2011. (June 2020) - Benwell, Matthew C; Davies, Andrew; Evans, Bethan; Wilkinson, Catherine
Based on a participatory research project which involved academics and young people at KCC Live, a community radio station in Merseyside, exploring the 1981 and 2011 riots in Liverpool, UK, this paper argues that co-produced research involving young people and radio provides an under-utilised avenue for research on historical and political geographies. Working together for a year in 2012–13, the academic and non-academic participants produced a radio documentary exploring how and why the 1981 riots in Liverpool occurred, and what we could learn from those historical events to help understand the more recent 2011 riots. Young people's capacities to engage with past events that took place before they were born, in order to reflect on and understand the political present, are seldom explored in research. The research that this paper is based on therefore provides an original and significant contribution to debates on conducting research with young people, in particular developing approaches to thinking through how young people engage with, and make sense of, politics and political activity, especially disruptive or insurgent activities like riots/urban uprisings. As a result, the paper makes an important contribution to work being done on the political capacities of young people; collective histories and memories in young people's understandings of politics, place, and space; and knowledges of urban uprisings. We argue that bringing children's/youth geographies into dialogue with political and historical geographies such as those discussed here is a useful avenue for future research.